ANALISIS ACTOR NETWORK THEORY DALAM IMPLEMENTASI KEARSIPAN DIGITAL DI INDONESIA - Bambang Aditio; Aldri Finaldi (Jurnal Riset Multidisiplin Edukasi, 2026)
The digital transformation of Indonesian records management through SRIKANDI (Integrated Dynamic Records Information System) faces a fundamental challenge at the actor-network mobilization stage. Although registered users reached 1,491,392 accounts, ANRI's 2025 Accountability and Performance Report reveals that 73%, or 1,089,341, are inactive users. This reflects a critical gap between formal enrolment and substantive mobilization within the Actor-Network Theory (ANT) framework. This article integrates findings from ANRI's 2024 external archival supervision reports to analyze mobilization barriers at the provincial and district/city levels. Supervision results indicate that while all 34 provincial governments possess live SRIKANDI accounts, only 23 provinces (67.6%) actively use the system with transactions exceeding 30% of regional work units. At the district/city level, of 84 sampled governments, 10 (11.9%) have not accelerated implementation at all. Drawing on Callon's (1986) ANT, this article argues that mobilization failure stems not from technical deficiencies alone, but from fragile actor-interest translation, regulatory-infrastructure ecosystem fragmentation, and the absence of organic mobilization mechanisms beyond regulatory pressure. The article offers strategic recommendations centered on strengthening actor value internalization, continuous technical capacity building, and digital records policy harmonization.